PROTOTYPE INFORMED CONSENT ELEKTRONIK UPTD PUSKESMAS BARON KAB. NGANJUK - Deni Luvi Jayanto; Surti Suharlikah; Vicky Djusmin (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2021)
The informed consent form that not properly recorded, difficult to read, became a problem that occurs in the inpatient registration unit, so it was better to do it by typing to made it clearer and easier to read. the use of electronic informed consent forms provides easy distribution so that it can save time and costs. the use of electronic informed consent forms made it easier for officers in digital archiving on computers so they didn't save a lot of files. The aim of the study was to recommended that UPTD Puskesmas Baron made an informed consent information system interface design accorded to user needs, based on interface design, color, and input. This study used observations at the UPTD Puskesmas Baron, by observing 2 inpatient registration officers, conducting interviews with 2 inpatient registration officers. The result of this study was the informed consent form at the UPTD Puskesmas Baron was manual which was used as an approval for action in inpatient registration, that approval of action must be carried out by Permenkes No. which it must be exist with the suitability of the officer. This research has suggested implementation, socialization and training for the application of electronic informed consent forms.